Activation of nuclear factor κB pathway and downstream targets survivin and livin by SHARPIN contributes to the progression and metastasis of prostate cancer. Issue 20 (12th June 2014) - Zhang, Yiming; Huang, Hai; Zhou, Huimin; Du, Tao; Zeng, Lexiang; Cao, Yi; Chen, Jieqing; Lai, Yiming; Li, Jin; Wang, Ganping; Guo, Zhenghui
Abstract : BACKGROUND: Nuclear factor κB (NFκB) signaling is strongly associated with tumor progression, and studies have shown that SHANK‐associated RH domain interacting protein (SHARPIN) is crucial for NFκB pathway activation. However, the expression and functions of SHARPIN in prostate cancer (PCa) have not yet been defined. METHODS: The expression of SHARPIN in PCa cell lines and tissues was evaluated with western blotting, quantitative real‐time polymerase chain reaction, and immunohistochemistry. After SHARPIN was silenced in the PCa cell lines, western blots were used to confirm that SHARPIN physically associated with components of the NFκB pathway and the downstream targets (survivin and livin). The functions of SHARPIN in cell proliferation, migration, and invasion in vitro were measured with 5‐(3‐carboxymethoxyphenyl)‐2‐(4, 5‐dimenthylthiazoly)‐3‐(4‐sulfophenyl)tetrazolium, inner salt (MTS), Transwell, and invasion assays, respectively. Flow cytometry was employed to evaluate cell apoptosis. Furthermore, tumorigenesis in vivo was examined with tumorigenicity assays. RESULTS: SHARPIN expression was upregulated in PCa cell lines and tissues. The knockdown of SHARPIN or incubation with Bay 11‐7082 (an NFκB inhibitor) led to dramatically decreased levels of phosphorylated IκBα and phosphorylated p65 in comparison with the control group. Downregulation of survivin and livin due to SHARPIN inhibition was attributable to transcriptional repression ( P  < .05). Decreases in cell viability, migration, invasion, and survival with a higher sensitivity to docetaxel in vitro and with repressed tumorigenesis in vivo were observed upon SHARPIN silencing, and this was consistent with the results from inhibition of the NFκB pathway and its downstream targets. CONCLUSION: The current study demonstrates that overexpression of SHARPIN promotes activation of the NFκB pathway and downstream targets survivin and livin, which potentially contributes to PCa development. Cancer 2014;120:3208–3218. © 2014 American Cancer Society . Abstract : SHANK‐associated RH domain interacting protein, a newly found oncogenic protein, contributes to prostate cancer progression via a cancer‐associated nuclear factor κB pathway. It may represent a novel therapeutic target for the treatment of advanced prostate cancer that is resistant to chemotherapy.